PENENTUAN KELAS KINERJA ASPAL KONDISI STANDAR BERDASARKAN DATA TEMPERATUR UDARA DARI STASIUN KLIMATOLOGI DI SELURUH INDONESIA - Tini Gustini; Madi Hermadi; Pio Ranap Tua Naibaho (LPPM, 2026)
The implementation of Performance Grade (PG) asphalt specifications has become increasingly important for supporting pavement construction and maintenance practices that account for the influence of climatic and traffic conditions on asphalt performance. However, the Superpave system requires continuous pavement temperature measurements over a minimum period of five consecutive years, while such data are not yet available on a national scale in Indonesia. This study aimed to determine the appropriate asphalt Performance Grade classification for standard traffic conditions in Indonesia using daily maximum and minimum air temperature data collected from 172 meteorological and climatological stations operated by the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG). Air temperature data were converted into pavement temperatures using the Superpave pavement temperature prediction equations. The maximum pavement temperature at a depth of 20 mm was used to determine the high-temperature performance grade, while the minimum pavement surface temperature was used to evaluate low-temperature performance requirements. The results indicate that most regions in Indonesia require PG 58 asphalt binders, whereas 13 locations require PG 64 binders. These findings suggest that the thermal conditions of Indonesian pavements generally remain within the operational range of PG 58, although several locations experience higher pavement temperatures that necessitate greater resistance to rutting and temperature-related distress. This study provides preliminary information on the spatial distribution of asphalt Performance Grades across Indonesia and may serve as a scientific basis for the development of a national PG map and the broader implementation of performance-based asphalt specifications for sustainable pavement infrastructure management.